Influence of different application rates of FGD gypsum and aeolian sand on CO2 and N2O emissions from cotton-capsicum saline-alkali soil - Chen, Yiwei; Luo, Fan; Guan, Yao; He, Xinghong; Wang, Jian; Fan, Debao; Gao, Rui (Frontiers in Environmental Science, 2024)
As two important greenhouse gases in the atmosphere, CO2 and N2O have been paid much attention to their environmental effects. As a large agricultural and population country in the world, agricultural soil is an important source of greenhouse gas emissions. In recent years, unreasonable agricultural measures will make the soil structure deteriorate and lead to the increase of saline-alkali cultivated land area. Therefore, the comprehensive utilization of saline-alkali land has practical significance for agricultural production and ecological environment safety in our country. In this study, the 11th Regiment of Alar City of the First Division of Xinjiang carried out field tests on saline-alkali cultivated land, and improved the saline-alkali cultivated land with desulfurized gypsum and aeolian sand. Six treatments were set up (blank treatment (CK) desulfurized gypsum 15 t/ha (LH), desulfurized gypsum 30 t/ha (LA), desulfurized gypsum 15 t/hamixed application (FL), Aeolian sand 15 t/ha (FH), and Aeolian sand 30 t/ha (FA)). The effects of different treatments on CO2 and N2O emission fluxes in cotton-pepper soil were observed. The results show that: (1) In the growth stage of cotton-pepper, compared with CK, soil moisture increased, and soil ammonium nitrogen decreased; The conductivity increases with the increase of desulphurized gypsum and the decrease of aeolian sand. The results showed that LA treatment had the best water retention effect and FA treatment had the best salt reduction effect. (2) Compared with CK, the cumulative CO2 emission fluxes of cotton soil under different treatments were CK > LH > FL > FH > LA > FA treatment, and those of pepper soil were CK > FL > LH > FH > FA > LA treatment. Among them, the inhibition effect of cumulative soil CO2 emission under LA and FA treatment reached a significant level. (3) Compared with CK, the cumulative N2O emission fluxes of LH, LA, FL, FH and FA treated soil in cotton field were CK > LA > LH > FH > FL > FA, and that of pepper soil was CK > FA > LH > LA > FL > FH. Among them, the inhibition effect of aeolian sand (FA and FH) on soil N2O cumulative emission reached a significant level. (4) Compared with CK, LH, LA, FL, FH and FA treatments reduced the comprehensive greenhouse effect of cotton field and pepper crops by inhibiting soil CO2 emission fluxes, among which FA treatment had the lowest comprehensive greenhouse effect. Therefore, the effects of different treatments on physicochemical properties and gas emissions of saline-alkali soil were comprehensively analyzed, and FA treatment had the best effect on inhibiting CO2 and N2O emissions and improving soil physicochemical properties.